Analisis Karakter Bahar dalam Novel Janji Karya Tere Liye: Antara “Pengorbanan dan Penyesalan" - Ziddan Fathul Hidayat; Rahma Aulia Priyanti (Kajian Administrasi Publik dan ilmu Komunikasi, 2024)
This study examines the character of Bahar in the novel "Janji" by Tere Liye, focusing on the themes of sacrifice and regret. The background of this research stems from the significance of literature in reflecting human life conflicts. The problem statement raised is how Bahar's character illustrates sacrifice and regret within his social context. The method employed is descriptive qualitative, with data collection through reading and literature review. The findings indicate that Bahar makes significant sacrifices by replacing Mas Puji's position who is detained, while also confronting the stigma of being an ex-convict. Despite experiencing regret, social support and love from Delima help him overcome feelings of inferiority and achieve intimacy. This research recommends that literary works like "Janji" can serve as a medium to understand individual psychological dynamics in a social context and as educational materials in literature studies to explore humanitarian values.